Oxidative Stress and Toxicity in Reproductive Biology and Medicine: Historical Perspectives and Future Horizons in Male Fertility - Henkel, Ralf (Advances in experimental medicine and biology, 2022)
Since the discovery by John MacLeod in 1943 that spermatozoa produce small amounts of hydrogen peroxide, a member of the so-called reactive oxygen species (ROS), the importance and functions of these highly reactive oxygen derivatives in physiology and pathology are a subject of numerous studies. It has been shown that they play essential roles, not only in causing oxidative stress if their concentration is excessively high, but also in triggering crucial cellular functions if their concentration is low. On the other hand, antioxidants counterbalance the action of ROS to maintain a fine balance between oxidation and reduction as an excessive amount of antioxidants leads to a condition called reductive stress and is as harmful as oxidative stress. This book "Oxidative Stress and Toxicity in Reproductive Biology and Medicine - A Comprehensive Update on Male Infertility" authoritatively summarizes the current knowledge of various causes of oxidative stress including various andrological conditions and environmental pollution as well as the physiological effects of ROS. Moreover, this book expands into the treatment of oxidative stress with antioxidants and phytomedicine, a rapidly developing area. As a first of its kind, this book also sheds light on the effects of the redox potential during the fertilization process and thus highlights the importance of the correct balance of oxidants and antioxidants, even in the culture medium in assisted reproduction. The editors have brought together an impressive group of renowned experts to share their knowledge on the topic of oxidative stress and its clinical management in andrology and assisted reproduction.